2014
DOI: 10.1038/ijo.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Infant antibiotic exposure and the development of childhood overweight and central adiposity

Abstract: Among boys, antibiotic exposure during the first year of life was associated with an increased risk of overweight and central adiposity in preadolescence, indicating that antibiotic stewardship is particularly important during infancy. Given the current epidemic of childhood obesity and the high prevalence of infant antibiotic exposure, further studies are necessary to determine the mechanisms underlying this association, to identify the long-term health consequences, and to develop strategies for mitigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
288
5
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(329 citation statements)
references
References 55 publications
22
288
5
7
Order By: Relevance
“…Those results are consistent with previous studies in humans, showing microbial changes in patients with type 2 diabetes (3,4) and increased risk of overweight among infants who were exposed to antibiotics during the first year of life (28). They are also consistent with mice models showing disruption of the microbiota, altered metabolic gene expression and induced adiposity following low dose antibiotic (25,26).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Those results are consistent with previous studies in humans, showing microbial changes in patients with type 2 diabetes (3,4) and increased risk of overweight among infants who were exposed to antibiotics during the first year of life (28). They are also consistent with mice models showing disruption of the microbiota, altered metabolic gene expression and induced adiposity following low dose antibiotic (25,26).…”
Section: Discussionsupporting
confidence: 82%
“…However, since change in the microbiota was previously demonstrated in humans in the entire spectrum of pathologies from obesity to insulin resistance and diabetes and since earlier studies showed antibiotic exposure as a risk factor for obesity (3,4,28), our results may support a possible hypothesis that change in the gut microbiota secondary to antibiotic exposure increase diabetes risk. The need for recurrent antibiotic exposures in addition to the lack of known direct harmful effect of antibiotics on the beta cells of the pancreas are in concordance with such a hypothesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The microbiota development is affected by a number of factors including genetics, mode of delivery and gestational age, antibiotic usage, breast feeding (BF)/formula feeding and long-term diet after weaning (Penders et al, 2006;Grönlund et al, 2007;Dominguez-Bello et al, 2010;Ladirat et al, 2013;Azad et al, 2014;Nylund et al, 2014;Olivares et al, 2014;Voreades et al, 2014). During the colonization process, facultative anaerobic bacteria, such as Enterobacteria, are gradually replaced by anaerobic bacteria, such as the genera Bifidobacterium, Clostridium and Bacteroides (Weber and Polanco, 2012;Matamoros et al, 2013;Arrieta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified associations between aberrant composition of microbiota in children and diseases including atopic diseases, autism, obesity, Crohn´s disease, celiac disease and food allergies (Kalliomäki et al, 2008;Cucchiara et al, 2009;Frank et al, 2011;Cheng et al, 2013;Azad et al, 2014;Nylund et al, 2015;Toh and AllenVercoe, 2015). Decreased diversity and richness of microbiota has been linked to several disorders (Turnbaugh and Gordon, 2009;Verdam et al, 2013;Nylund et al, 2015).…”
Section: Introductionmentioning
confidence: 99%